DIGITAL TRANSFORMATION OF TRADITIONAL BANKS: COLLABORATION STRATEGY WITH FINTECH FOR FINANCIAL INCLUSION - Adhista Setyarini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Digital transformation undertaken by traditional banks through collaboration strategies with fintech has become an effective approach to support financial inclusion. In facing the challenges of technological change and increasingly digital consumer needs, traditional banks utilise fintech to expand access and deliver more innovative financial services. This collaboration integrates the strengths of traditional bank networks and fintech's advanced technology, enabling them to reach underserved segments of society, such as small businesses and rural communities. This results in more inclusive digital financial solutions, such as microloans, app-based financial management, and financial literacy education. This approach not only improves access to financial services, but also drives innovation and efficiency in the industry. Therefore, this collaborative strategy is an important step that facilitates the transformation of traditional banks in supporting global financial inclusion.